Jurnalisme Politik: Keberpihakan Media dalaim Pemilu 2004 - - Masduki (Jurnal Ilmu Sosial dan Ilmu Politik, 2004)
The idea of independent political journalism failed to perform during the 2004 general election in Indonesia. Instead of keeping equal distance from the bourgeois dan capitalist interest, a number of the journalists even proud to be able to serve them.